SINTESIS BIODIESEL DARI MINYAK KEDELAI MELALUI REAKSI TRANSESTERIFIKASI DENGAN KATALIS CaO/NaOH - Syarifuddin Oko; Mustafa Mustafa; Andri Kurniawan; Danu Willain (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2021)
Biodiesel is an alternative fuel produced from vegetable oils such as soybean oil by the method of transesterification with the help of catalysts. This research uses a heterogeneous catalyst, CaO which is derived from an eggshell through a calcination process is impregnated with NaOH so that the CaO cavity can be filled by Na ions in order to increase the alkaline nature of the catalyst. The increase in biodiesel yield can be done by varying the catalyst concentration of CaO/NaOH and mole ratio of soybean oil / methanol. CaO catalyst obtained from calcination of chicken eggshell was impregnated with 5% NaOH (w/v) as much as 50 ml into 50 g of CaO gradually, stirred while accompanied by heating, and continued calcination at 300 ℃ for 3 hours. Biodiesel synthesis was carried out by esterification and transesterification using methanol, biodiesel synthesis was done by varying the mole ratio of soybean oil with methanol 1: 6; 1: 9; 1:12 and catalyst concentration 0.5; 1 and 1.5% at 60-65°C for 3 hours. The best result was obtained with a yield of 86.7860% in the mole ratio of oil with methanol 1:12 with a catalyst concentration of 1% based on oil weight, density of 0.8899 gram / ml, viscosity of 3.5208 Cst, acid number of 0.33 mg KOH/g max and water content of 0.0095% and this is in accordance with SNI 7182: 2015 standards.